Ultrasound-guided injection of the hip: Cadaveric description for the lateral approach - Mezian, Kamal; Ricci, Vincenzo; Mittal, Nimish; Novotný, Tomáš; Chang, Ke-Vin; Özçakar, Levent; Naňka, Ondřej (PM & R, 2023)
BACKGROUND: Ultrasound (US)-guided intraarticular hip joint injections are commonly performed using an in-plane anterior approach, which has several limitations. OBJECTIVE: To describe and report a "lateral" (lateral to medial) approach for US-guided intraarticular hip injection. DESIGN: Cadaveric investigation. SETTING: Academic institution, department of anatomy. PARTICIPANTS: One cadaveric specimen. METHODS: Both hips of a single cadaver were injected using the US-guided lateral approach. In the left hip, the needle was inserted and kept in situ. The right hip was injected with white-colored water-diluted latex dye. Subsequently, a layer-by-layer anatomical dissection was performed. MAIN OUTCOME MEASURES: Presence and distribution of latex dye and location of needle tip within the joint capsule of the hip. RESULTS: Anatomical dissection of the left and right hips confirmed the correct intraarticular position of the needle tip and the placement of the latex dye, respectively. During layer-by-layer dissection of the left hip, positions of the lateral cutaneous nerve and the lateral circumflex femoral artery were observed anterior to the needle, 30 mm for the nerve and 8 mm for the artery. CONCLUSIONS: This preliminary study demonstrated that the US-guided lateral approach is a convenient technique to access the hip joint in a cadaveric specimen. Compared with the "classical" anterior technique, the lateral approach may provide several advantages, including improved needle visibility, theoretically decreased risk of vascular injury, and less risk of needle contamination. Because injury to the lateral epiphyseal arteries is possible when lateral approach is used, caution is required, especially in children. These preliminary conclusions will need to be validated in future/larger clinical studies.
Keywords: Child; Latex; Ultrasonography, Interventional; mrtvola; latex; Cadaver; intervenční ultrasonografie; Hip Joint; Ultrasonography; ultrasonografie; Humans; lidé; kyčelní kloub; dítě